Ingresos operacionales de la Empresa Comercial “Don Vargas” del cantón Babahoyo, provincia de Los Ríos en el periodo 2022 y 2023. - Varas Vega, Johan Alexander (2024)
The case study was developed in the commercial company "Don Vargas" of the Babahoyo canton, Los Ríos province, with the aim of determining the company's operating income, by reviewing the financial statements to know the variation in the periods 2022-2023. The methodology used was based on a quantitative approach, non-experimental design, inductive method, descriptive and documentary research types, as well as control survey techniques, documentary review and financial analysis, together with their respective research instruments. The results were: operating income in 2023 was considerably reduced (-41.68%) compared to the previous year; operating profitability in 2022 was 6.82% while net was 5.95%; income did affect the company's profitability in 2023 because it did not make any profit, evidenced by the operating margin of 0.37% since net did not exist; and the control risk applied to operating income is not favorable, because it has a moderate risk of 53% due to different weaknesses in its management. In conclusion, the company's operating income had a negative variation, because in 2023 it decreased by -41.68% compared to the previous year, a negative aspect that can condition its liquidity. Income has had an impact on the organization's profitability because the profitability analysis through financial ratios presented unfavorable results for the period 2023 compared to 2022.